Counter-Terrorism The Ethical Issues - Miller, Seumas; Henschke, Adam; Feltes, Jonas (Edward Elgar Publishing, 2021)
This insightful book provides an analysis of the central ethical issues that have arisen in combatting global terrorism and, in particular, jihadist terrorist groups, notably Al Qaeda, Islamic State and their affiliates. Chapters explore the theoretical problems that arise in relation to terrorism, such as the definition of terrorism and the concept of collective responsibility, and consider specific ethical issues in counter-terrorism.